STUDI LITERATUR TANAMAN WALISONGO (Schefflera arboricola) SEBAGAI TANAMAN PENETRALISIR POLUSI UDARA DAN BIOAKTIVITASNYA - WIJAYANTI, ERNA (Jurusan Pendidikan Biologi, Fakultas Ilmu Pendidikan, Universitas Timor, 2023)
Air pollution can cause health problems either directly or indirectly. This air pollution can occur indoors or outdoors. One type of plant that can reduce air pollution is the walisongo plant. In Indonesia, the walisongo plant (Schefflera arboricola) is also called the umbrella tree, which is a member of the Araliaceae family and has the potential as a medicinal ingredient. Information about this plant is still limited, so this research is essential to do. This research is a literature study research. The data was obtained online using the keywords walisongo plant or Schefflera arboricola. The data obtained were reviewed and synthesized. The walisongo plant originated from Taiwan and Hainan (China), spreading to various regions in Asia, tropical Africa, Florida, and Hawaii. This plant is easy to cultivate naturally (seeds) and artificially (cuttings and grafts). This plant is useful as an ornamental plant and an air biofilter to function as a neutralizer of air pollution. In addition, this plant has bioactive compounds found in its leaves and stems. The walisongo plant can be used as a neutralizer of air pollution, and its bioactive compounds can be used as medicinal ingredients.